ASSESSMENT OF THE ABILITY TO PROVIDE ENTERPRISE'S ECONOMIC SECURITY BASING ON THE PROCESS APPROACH (Development Service Industry Management, 2024)
The assessment of an enterprise's ability to provide economic security based on the process approach is proposed to be carried out by separately evaluating the enterprise's need for economic security and the possibility of using a process approach in enterprise management, with subsequent combination of the obtained assessments in an evaluation matrix.To assess the enterprise's need for economic security, a tabular form was developed based on the control question method. This table presents a set of questions, answer options for each question, and a corresponding score for each option. A procedure for transitioning from a point-based evaluation to a normalized assessment on a unit scale is proposed. Recommendations have been developed for interpreting the obtained partial and overall assessments to qualitatively evaluate the enterprise's need for economic security.A tabular form was developed based on the control question method to assess the possibility of using a process approach in enterprise management. This table presents a set of questions, answer options for each question, and a corresponding score for each option. To create an aggregate assessment of the possibility of using a process approach in enterprise management, a procedure for transitioning from a point-based evaluation to a normalized assessment on a unit scale was proposed. Recommendations have been developed for interpreting the obtained partial and overall assessments to qualitatively evaluate the possibility of using the process approach in enterprise management.To determine the possibility of providing the economic security of the enterprise based on the process approach, a matrix was developed by combining assessments of the enterprise's need for economic security and the possibility of using the process approach in management. Each of the four quadrants of this matrix is described, and management recommendations are provided for each quadrant regarding the possibility of using the process approach to provide the enterprise's economic security.
Keywords: providing; economic security; enterprise; process approach; assessment; evaluation form; matrix